(untitled) - Stevenson, William D. (New York, 1982)
The approach is to develop the thinking process of the student in reaching a sound understanding of a broad range of topics in the power-system area of electrical engineering. Another goal is to promote the student's interest in learning more about the electric-power industry. The objective is not great depth, but the presentation is thorough enough to give the student the basic theory at a level that can be understood by the undergraduate.
Keywords: Electric power distribution,Phân phối điện